Laparoscopic Pyeloplasty - Our Early Experience (Journal of Paediatric Surgeons of Bangladesh, 2014)
Objectives: To present our initial experience with laparoscopic pyeloplasty and to evaluate the safety and short-term outcome of this technique.Methods: Five patients underwent laparoscopic dismembered pyeloplasty for the management of ureteropelvic junction obstruction (UPJO) at Chittagong between July2007 to Mach2009. Patient age at surgery was 822 years. There were two boys and three girls. All had unilateral UPJO with a normal contralateral kidney. We used 5 mm instruments for grasping, blunt dissection, incising and suturing to facilitate safe and precise surgery. The outcome was measured by the operative time, perioperative complications and resolution of obstruction and symptoms.Results: Mean operative time was 195 minutes (range 175220 min). No major perioperative complications occurred in any cases. Overall, successful resolution of UPJO was observed in all the five cases evident by renogram.Conclusions: Laparoscopic pyeloplasty represents a safe and effective option in the surgical treatment of UPJO.DOI: http://dx.doi.org/10.3329/jpsb.v1i1.19448